Programa educativo aprendizaje significativo en el logro de la competencia construye interpretaciones históricas en el área de Ciencias Sociales en estudiantes de cuarto grado de secundaria Institución Educativa Sagrado Corazón distrito de Iquitos 2024 - Panduro Chavez, Luis Fernando (2025)
The purpose of the research focused on assessing the influence of meaningful learning on the variable "constructing historical interpretations." Methodologically, it adopted a quasi-experimental, evaluative approach with an entrance and exit test. The population consisted of 170 fourth-grade secondary school students, from which a census or convenience sample of 66 was drawn. The survey technique was used, and a multiple-choice test was used as the instrument. Data processing was performed using the Shapiro-Wilk statistic. Hypothesis testing was performed using the Wilcoxon rank test, where significance values below 0.05 were mostly reported; thus, a substantial difference was found between the results of the initial and exit tests. The research concludes that with a p-value of 0.000 and a Z-value of -5.324, it is proven that the Meaningful Learning Educational Program produces a significant improvement in the development of the competency constructing historical interpretations in the area of Social Sciences.